ESENSI PANCASILA DALAM KEBERADABAN BANGSA : STUDI KASUS BANJIR DI JAWA BARAT - Nafisha Khayla (Universitas Negeri Gorontalo, 2025)
Analysis of the essence of Pancasila in the process of shaping Indonesian society, using a case study of community solidarity in facing floods in West Java in 2023. As the foundation of the state, Pancasila is not only understood in terms of legal rules, but also as the root of moral and social values that govern community behavior. According to Kaelan (2017), Pancasila can serve as ethical guidance that controls the life of the nation and state. This type of research will use a descriptive qualitative approach with a case study method. Data will be collected from various academic sources and online news related to the application of Pancasila values in community life. According to Sianturi and Dewi (2017), “in principle, the application of Pancasila values in everyday life enables the development of character and social solidarity.” The results of the study show that the values of each principle of Pancasila appear in the actions of the community in facing disasters, such as tolerance among religious communities, cooperation, deliberation to reach consensus, and helping fellow human beings. This confirms that Pancasila remains relevant as the moral and social foundation of the nation amid the challenges of globalization and technological developments.